New trends for staging and therapy for localized gastroesophageal cancer: the role of PET - Lordick, Florian; Ott, Katja; Krause, Bernd Joachim (Annals of oncology, 2010)
Treatment options for localized gastroesophageal cancers reach from limited resection to multimodality treatment. Accurate clinical assessment, prognostic and predictive information are needed to select the most appropriate treatment approach. Positron emission tomography (PET) in combination with computed tomography (CT) in a hybrid imaging modality PET-CT may refine the staging accuracy and add prognostic information. Moreover, experiences from diverse centers indicate that PET also might improve significantly the assessment of response to preoperative chemotherapy and chemoradiotherapy. This article outlines the current value of PET in the staging and multidisciplinary care of gastroesophageal cancer. At this stage, it remains unclear whether the prognosis of patients can be improved by implementing PET in the management of localized disease. Prospective multicenter studies have to be carried out to validate metabolic cut-off values and to prove the benefit of PET-guided treatment decisions.
Online veröffentlicht am 6. Januar 2020
Gesehen am 18.04.2023